Efektivitas Strategi KomandanTe Stelsel PDI Perjuangan di Jawa Tengah pada Pemilu 2024 - Oktavania, Dyah Ajeng; Sutjiatmi, Sri; Habibullah, Akhmad (Nakhoda: Jurnal Ilmu Pemerintahan, 2024)
Indonesian Democratic Party of Struggle (PDI-P) In the 2024 Legislative Election, implemented the KomandanTe Stelsel strategy in Central Java, the KomandanTe Stelsel System is a political strategy implemented by the Indonesian Democratic Party of Struggle (PDI-P). This strategy is based on the principle of mutual cooperation and organized division of tasks to party cadres, by assigning each legislative candidate (caleg) to manage a certain area as a power area or combat area. which has a varied impact on the acquisition of legislative seats in various districts and cities. This study aims to evaluate the effectiveness of this strategy in mobilizing support and strengthening internal party solidarity. This research method. Using a qualitative descriptive approach and utilizing data from secondary sources, the analysis was carried out by comparing information from various sources and seeing the suitability between the data and the research objectives. The results of the study showed varying impacts in various regions where some regions experienced an increase, decrease, or stability in the acquisition of legislative seats. The variation in results in each district/city shows that this system requires a more in-depth evaluation, as well as more appropriate adjustments so that it can be better implemented in all regions. Overall, although the KomandanTe Stelsel is a significant innovation in managing competition between candidates and strengthening party solidarity, continuous evaluation and adjustment strategies are needed to optimize its impact in the future.